Sequential and direct ionic excitation in the strong-field ionization of 1-butene molecules. Issue 21 (18th May 2018) - Schell, Felix; Boguslavskiy, Andrey E.; Schulz, Claus Peter; Patchkovskii, Serguei; Vrakking, Marc J. J.; Stolow, Albert; Mikosch, Jochen
Abstract : We find a striking transition in excited ion state formation when changing the wavelength in strong-field ionization: from sequential excitation (left) to direct ionization (right). Abstract : We study the Strong-Field Ionization (SFI) of the hydrocarbon 1-butene as a function of wavelength using photoion-photoelectron covariance and coincidence spectroscopy. We observe a striking transition in the fragment-associated photoelectron spectra: from a single Above Threshold Ionization (ATI) progression for photon energies less than the cation D0 –D1 gap to two ATI progressions for a photon energy greater than this gap. For the first case, electronically excited cations are created by SFI populating the ground cationic state D0, followed by sequential post-ionization excitation. For the second case, direct sub-cycle SFI to the D1 excited cation state contributes significantly. Our experiments access ionization dynamics in a regime where strong-field and resonance-enhanced processes can interplay.